IMPLEMENTASI PROFESIONAL LIABILITY PADA TRANSAKSI JUAL-BELI ONLINE TAS SIGNATURE BRANDED - Ni Luh Sri Mahendra Dewi (Widyasrama, 2021)
A branded signature bag is a definition of authentic authenticity to a product, whether it’s from the design, product quality, factory, product processing, product details are original or genuine. Even in the production of a branded bag, mistakes can occur which can reduce the value and aesthetics of the bag, so the term defect appears. However, this product is still sold to boutique suppliers outside the official retail store with several conditions, namely the packaging is not accompanied by an ID card and serial number and barcode like the original. However, when traced for the quality of the goods, it is guaranteed to be 100% authentic, exactly the same as the original. How is the implementation of professional liability for purchasing signature defec bags through the official online website where the product category sold is defective but categorized as original with a price of tens of millions, what are the implications for state income through Luxury Goods Tax or Customs which are not attached to defective branded signature products. From a fairness perspective, how can a consumer get their rights in purchasing a branded signature bag that can be said to be original? The research is accompanied by the implementation of descriptive analysis methods, the topic of this research philosophically raises the essence of the original product or the original defective signature.